ADOLESCENTS’ ATTITUDES TO SPIRITUAL VALUES:TENDENCIES OF CHANGE - Martišauskienė, Elvyda (Acta Paedagogica Vilnensia, 2011)
The article focuses on the comparison of the data acquired during the researches that were conducted in the same schools in 1999 and 2009. The research results highlighted tendencies of change in adolescents’ attitudes towards values (7th–9th formers). It was established that adolescents tend to acknowledge spiritual values prioritising moral values such as dignity, honesty and sensitivity. These values received highest evaluations both in real and virtual situations. The honesty received the most stable evaluation, whereas acknowledgement of dignity showed the biggest increase, especially in evaluation of respect (38 %). On the other hand, evaluation of sensitivity, especially that of sympathy, showed a downward tendency (12 %). The smallest number of adolescents acknowledge altruism (the highest acknowledgment decreased by 10–12 % in the virtual situation) and faith (a fall of 8–11 % was observed in both real and virtual situations). However, a sense of spiritual unity in the microenvironment (as well as its expression) remains of high importance among one third of adolescents and, thus, creates a more favourable perspective. A change in teenagers’ attitudes towards sensitivity to beauty was observed: a sense of humour is evaluated highest and an upward tendency was observed (10 %), whereas a fall in evaluation of admiration (6–14 %) was identified. Similar tendencies are observed in attitudes towards cleverness: the respondents highly acknowledge the purport of life several times as rare as intellectuality, though the ratings of the latter also showed a downward trend (7–11 %). The same evaluation is characteristic of a number of values such as responsibility, when assuming of responsibility for own actions, fulfilment of duties were evaluated several times lower than non-compliance with negligence; solidarity, when acknowledgement of tolerance increased, whereas that of balancing of interests decreased; creativity, when in real situations it is practically eliminated in real situations (pointed out by 1–5 % of the respondents). Adolescents’ attitudes towards spiritual values only partially meet challenges of time and a downward tendency in acknowledgement of a big number of spiritual values pose educational problems that ask for immediate solutions.